T follicular helper cells expansion in transplant recipients correlates with graft infiltration and adverse outcomes - Désy, Olivier; Béland, Stéphanie; Thivierge, Marie-Pier; Marcoux, Meagan; Desgagnés, Jean-Simon; Bouchard-Boivin, François; Gama, Alcino; Riopel, Julie; Latulippe, Eva; De Serres, Sacha A. (Frontiers in Immunology, 2024)
The process of immunization following vaccination in humans bears similarities to that of immunization with allografts. Whereas vaccination aims to elicit a rapid response, in the transplant recipient, immunosuppressants slow the immunization to alloantigens. The induction of CD4+CXCR5+ T follicular helper (Tfh) cells has been shown to correlate with the success of vaccine immunization. We studied a cohort of 65 transplant recipients who underwent histological evaluation concurrent with PBMC isolation and follow-up sampling to investigate the phenotypic profiles in the blood and allotissue and analyze their association with clinical events. The proportion of circulating Tfh cells was heterogeneous over time. Patients in whom this compartment increased had lower CCR7-PD1+CD4+CXCR5+ T cells during follow-up. These patients exhibited more alloreactive CD4+ T cells using HLA-DR-specific tetramers and a greater proportion of detectable circulating plasmablasts than the controls. Examination of baseline biopsies revealed that expansion of the circulating Tfh compartment did not follow prior intragraft leukocyte infiltration. However, multicolor immunofluorescence microscopy of the grafts showed a greater proportion of CXCR5+ T cells than in the controls. CD4+CXCR5+ cells were predominantly PD1+ and were in close contact with B cells in situ. Despite clinical stability at baseline, circulating Tfh expansion was associated with a higher risk of a composite of anti-HLA donor-specific antibodies, rejection, lower graft function, or graft loss. In otherwise stable patients post-transplant, circulating Tfh expansion can identify ongoing alloreactivity, detectable before allograft injury. Tfh expansion is relevant clinically because it predicts poor graft prognosis. These findings have implications for immune surveillance.